21st Century Skills as an Effort to Strengthen Civic Skills in Pancasila Education at MTs Negeri 2 Surakarta - Akbar, Fariq; Sumardjoko, Bambang (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to describe the application of 21st-century skills (6C) critical thinking, creativity, communication, collaboration, citizenship, and character as an effort to strengthen civic skills in Pancasila Education at MTs Negeri 2 Surakarta. Specifically, it analyzes how 6C-based learning practices reveal indicators of students' civic skills, including intellectual and participatory skills, teachers' pedagogical strategies in structuring learning activities, and supporting and inhibiting factors that influence the strengthening of civic skills in the madrasah environment.Methodology: This research uses a qualitative approach with a case study design. Data were collected through in-depth interviews, field observations, and document analysis using triangulation of sources, methods, and time to ensure data validity. The participants consisted of Pancasila Education teachers, students, and the principal and vice principal of the madrasah. Data were analyzed through stages of reduction, presentation, and inductive conclusion drawing.Results: The findings show that the application of 21st-century skills in Pancasila Education strengthens students' civic skills through critical thinking, group collaboration, reflective communication, and active participation. Teachers' pedagogical strategies that integrate constructivism and deliberative democracy theories effectively foster students' intellectual abilities and social responsibility. Supporting factors include a religious and collaborative school culture and a curriculum emphasizing moral and spiritual values, while obstacles involve limited facilities, time, and varied student engagement.Applications/Originality/Value: This study contributes theoretically to developing a 6C-based Pancasila Education model relevant to the madrasah context. Practically, it serves as a reference for teachers to design contextual, participatory, and character-oriented learning. Its originality lies in integrating 21st-century competencies with Islamic and national values to form critical, religious, and responsible citizens.